2000
DOI: 10.1212/wnl.54.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Headache and major depression

Abstract: The contrasting results regarding the relationship of major depression with migraine versus other severe headaches suggest that different causes may underlie the co-occurrence of major depression in persons with migraine compared with persons with other severe headaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
316
4
19

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(361 citation statements)
references
References 24 publications
22
316
4
19
Order By: Relevance
“…In contrast, the hypothesis of shared causes would predict that each disorder might increase the risk of first-time occurrence of the other. Some studies suggested bidirectional influences between migraine and major depression, with each disorder increasing the risk of first onset of the other [6,7]. Moreover, the fact that prevention of migraine attacks might benefit from treatments with some antidepressant agents ( Table 2) supports the presence of shared mechanisms.…”
Section: Migraine and Psychiatric Disordersmentioning
confidence: 99%
“…In contrast, the hypothesis of shared causes would predict that each disorder might increase the risk of first-time occurrence of the other. Some studies suggested bidirectional influences between migraine and major depression, with each disorder increasing the risk of first onset of the other [6,7]. Moreover, the fact that prevention of migraine attacks might benefit from treatments with some antidepressant agents ( Table 2) supports the presence of shared mechanisms.…”
Section: Migraine and Psychiatric Disordersmentioning
confidence: 99%
“…A recent study examined the association between migraine and personality profile, taking into account history of coexisting psychiatric disorders [27]. Data obtained from an epidemiologic study of young adults also suggested that migraine was associated with neuroticism, but not with extraversion or psychoticism, and that an excess of 25% of patients with migraine alone (uncomplicated by psychiatric comorbidity) scored in the highest quartile of neuroticism.…”
Section: S118mentioning
confidence: 99%
“…Completed suicide (Rafnsson, Olafsson et al 2001) is known to occur more than expected in people with epilepsy. Likewise, the relationship between MA and depression (Breslau, Schultz et al 2000) is bidirectional and suicide attempt (Breslau, Schultz et al 2000) is associated with prevalent MA. Combined, these associations suggest a common underlying genetic or acquired brain dysfunction.…”
Section: Introductionmentioning
confidence: 99%